Performance and effectiveness of School Management Committees (SMC) of BRAC schools - Sultan, Sania (BRAC Research and Evaluation Division (RED), 2020)
The study examined the School Management Committees of NFPE schools. With the knowledge of supposed ineffectiveness of the committees, the goal was to find out what practices could be reinstated, or what could be done differently in order to have proper and effective management committees in all BRAC schools. By conducting focus Group Discussions with eight Management Committees from two NFPE areas, the study determined a few areas of concern, such as committee formation, participation, orientation, monitoring, supervision and so forth.